Acute encephalopathy with biphasic seizures and late reduced diffusion (central sparing type)—MRI and MR spectroscopy findings - Ranjan, Rahul S (Indian J Radiol Imaging, 2019)
Acute encephalopathy with biphasic seizure and late reduced diffusion (AESD) is a clinico-radiologic syndrome of acute encephalopathy characterized by biphasic seizure and altered consciousness in acute phase followed by restricted diffusion in bilateral cerebral parenchyma on magnetic resonance imaging (MRI) in the subacute stage. Here, we present the MRI and magnetic resonance spectroscopy (MRS) findings in a case of AESD presenting in 4-year child and diagnosed based on clinico-radiological correlation.